EKSISTENSI PERSIDANGAN ONLINE DITENGAH PANDEMI COVID19 DALAM PERKARA PIDANA DI INDONESIA - Hanafi Hanafi; Muhammad Syahrial Fitri; Fathan Ansori (Al-Adl : Jurnal Hukum, 2021)
Following the background, the problems in this study are, first, the mechanism for implementing procedural law in E-Court for criminal cases in Indonesia, secondly how E-Court accommodates the process of proof in criminal cases in Indonesia. The method used in this research is pure legal research, which refers to and bases on legal norms and principles, applicable laws and regulations, legal theories and doctrines, jurisprudence, and other literature that are relevant to the topic. The results of this study are, firstly, the mechanism for implementing E-Court procedural law is regulated in the Supreme Court Regulation 4/2020 on the Administration and Trial of Criminal Cases in Electronic Courts provides 2 (two) alternatives for conducting trials in criminal cases, namely Normal Courts and Electronic Courts. Such matters are not previously regulated in the Criminal Procedure Code or other procedural regulations. Second, concerning the process of proofing evidence in criminal cases in E-Court still follows the provisions of the normal criminal procedure law and has the same value or power of evidence as normal trials.